MORPHO-DYNAMIC AND FUNCTIONAL BREAST MRI FEATURES IN THE ASSESSMENT OF DUCTAL CARCINOMA IN SITU (DCIS) AND INVASIVE DUCTAL CARCINOMA (IDC) IN POSTMENOPAUSAL FEMALE PATIENTS: BREAST MRI IN DCIS AND IDC IN POSTMENOPAUSAL PATIENTS - Mihajlović, Marko; Đajić, Anđela; Krušac, Iva; Dimitrijević, Dejan; Raspopović,, Luka; Nadrljanski , Mirjan (Medical Research, 2024)
ABSTRACTIntroduction: Most frequent histologic types of breast cancer include invasive ductal carcinoma (IDC) and its most common precursor: ductal carcinoma in situ (DCIS). Based on morpho-dynamic and functional parameters: lesion size, initial signal intensity enhancement (wash-in), time-intensity curve (TIC) type, apparent diffusion coefficient (ADC), and positive enhancement integral (PEI), breast dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) allows the differentiation between IDC and in situ lesions in postmenopausal female patients.Methods: A single-center retrospective study included 40 postmenopausal female patients with histopathologically confirmed diagnosis (DCIS n1=20; IDC n2=20), examined with full diagnostic protocol (FDP) on 1.5T and 3T MRI scanners. The SPSS 21.0 software package was used for the statistical analysis of the defined parameters in two predefined subgroups.Results: Tumor size was significantly larger (p